The lived experience of undergraduate student parents: roles compatibility challenge - Lucchini-Raies, Camila; Márquez-Doren, Francisca; Herrera-López, Luz María; Valdés, Camila; Rodríguez, Náyade (Investigación y Educación en Enfermería, 2018)
Objective. To reveal the meanings attributed by university students to their experience of becoming a mother/father during their studies. Methods. A phenomenological study was conducted with students at a private Chilean University. Sixteen students from different undergraduate careers (eight women and eight men) participated in in-depth interviews, which were recorded. A phenomenological analysis of the data that followed the Streubert method was carried out, ensuring rigor by the criteria established by Guba and Lincoln during the research process. The ethical aspects were addressed through the process of informed consent, confidentiality and methodological rigor. Results. The phenomenon of becoming a mother/father during the university studies was revealed through four central themes: Emotions in conflict; Internal mobilization to address the situation; Position oneself in a new role; and Need for support. The central contribution of the study is the revelation of the transformation process towards the integrated role of father/mother-student. Conclusion. This study provides qualitative evidence that contributes to a comprehensive understanding of the experience of becoming a mother/father during the university studies; concluding that this life experience is presented as a process of role compatibility, which is necessary to support. For this, it is necessary to make visible the role of parents/students in university policies, with the aim of providing concrete support during this process of parallel transition in the lives of young people. How to cite this article: Lucchini-Raies C, Márquez-Doren F, Herrera-López LM, Valdés C, Rodríguez N. The lived experience of undergraduate student parents: roles compatibility challenge. Invest. Educ. Enferm. 2018; 36(2):e03.